Prevalência dos principais vírus respiratórios em bovinos da raça holandesa, no estado do Paraná - Sponchiado, Daniella [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
A serological survey of the following respiratory viruses: Bovine Herpesvirus 1 (BoHV-1), Bovine Viral Diarrhea Virus (BVDV), Bovine Parainfluenza Virus Type 3 (bPIV-3) and Bovine Respiratory Syncytial Virus (BRSV) in Holstein cattle black and White (HPB), raised in Paraná state was performed. 714 blood samples were collected from the jugular vein of cattle not vaccinated for the studied agents, over six months of age, from 26 dairy herds, distributed in 17 municipalities of Paraná state. Alongside the collection, a questionnaire was used for each property studied in order to assess the risk factors associated with the viruses examined. The serum samples were subjected to the diagnosis test of virus neutralization at the Laboratory of Viral Diseases of Cattle of the Biological Institute of São Paulo. Frequencies of 22.3%; 35.8%; 80.4% and 93.5% of seropositive cattle were observed and 65.3%, 88.5%, 96.1% and 100% of the seropositive properties BoHV-1, BVDV, bPIV-3 and BRSV, respectively. The co-infection that occurred most frequently was the bPIV-3 and BRSV (37.1%). After logistic regression analysis, risk factors associated with BoHV-1 were cattle with more than 48 months of age (OR = 15.012; 95% CI 7.500 to 30.051), property area 26-50 hectares (OR = 11.328; 95% CI 2.482 – 51.697), stocking higher than three animals per hectare (OR = 1.026; 95% CI 0.370 to 2.847), cattle entry percentage higher than 10% (OR = 52.520 entry; 95% CI 13.269 to 207.876); for BVDV were cattle older than 48 months (OR = 4.407; 95% CI 2.456 to 7.906), Southwest region (OR = 52.388; 95% CI 4.629 to 5892.873), semi-intensive production system (OR = 1.333; 95% CI 0.261 to 6.815),property with fewer animals than or equal to 50 (OR = 16.682; 95% CI 3.218 to 86.481), a percentage of cattle entry higher than 10% (OR = 17.56; 95% CI 7.613 – 40.506) and neighboring pasture sharing (OR = 9.148; 95% CI 3.751 to 22.310); for bPIV-3 cattle older than 48 months ...

Realizou-se levantamento sorológico dos seguintes vírus respiratórios Herpesvírus Bovino 1 (BoHV-1), Vírus da Diarreia Viral Bovina (BVDV), Vírus da Parainfluenza Bovina Tipo 3 (bPIV-3) e Vírus Respiratório Sincicial Bovino (BRSV) em bovinos da raça Holandesa variedade Preta e Branca (HPB), criados no estado do Paraná. Colheram-se 714 amostras de sangue da veia jugular de bovinos, não vacinados para os agentes estudados, com mais de seis meses de idade, de 26 propriedades leiteiras, distribuídas em 17 municípios do estado do Paraná. Paralelamente à colheita, aplicou-se um questionário para cada propriedade estudada, com a finalidade de avaliar os fatores de risco associados aos vírus examinados. As amostras sorológicas foram submetidas ao teste de diagnóstico de virusneutralização no Laboratório de Viroses de Bovinos do Instituto Biológico de São Paulo. Foram observadas prevalências de 22,3%; 35,8%; 80,4% e 93,5% de bovinos sororreagentes e 65,3%, 88,5%, 96,1% e 100% das propriedades reagentes para BoHV-1, BVDV, bPIV-3 e BRSV, respectivamente. A coinfecção que ocorreu com maior prevalência foi a bPIV-3 e BRSV (37,1%). Após análise de regressão logística, os fatores de risco associados ao BoHV-1 foram: bovinos com idade maior que 48 meses (OR=15,012; IC95% 7,500 – 30,051), área da propriedade 26 a 50 hectares (OR=11,328; IC95% 2,482 – 51,697), lotação maior de três bovinos por hectare (OR=1,026; IC95% 0,370 – 2,847), percentual de entrada maior que 10% de bovinos (OR=52,520; IC95% 13,269 – 207,876); para o BVDV foram: bovinos com idade maior que 48 meses (OR=4,407; IC95% 2,456 – 7,906), região Sudoeste (OR=52,388; IC95% 4,629 – 5892,873), sistema de produção semi-intensivo (OR=1,333; IC95% 0,261 – 6,815), propriedade com número de animais menor ou igual a 50 bovinos (OR=16,682; IC95% 3,218 – 86,481), percentual de entrada maior que 10% de bovinos (OR=17,56; IC95% 7,613 – 40,506) e ...
Prevalence of major respiratory viruses in casttle Holstein, in Paraná state
Keywords: Bovino - Criação; Bovino de leite; Estudos transversais; Viroses em animais; Virus do herpes em animais; Virus diseases in animals